2019
DOI: 10.3847/1538-4357/ab184e
|View full text |Cite
|
Sign up to set email alerts
|

On the Detectability of Visible-wavelength Line Emission from the Local Circumgalactic and Intergalactic Medium

Abstract: We describe a new approach to studying the intergalactic and circumgalactic medium in the local Universe: direct detection through narrow-band imaging of ultra-low surface brightness visible-wavelength line emission. We use the hydrodynamical cosmological simulation EAGLE to investigate the expected brightness of this emission at low redshift (z 0.2). Hα emission in extended halos (analogous to the extended Lyα halos/blobs detected around galaxies at high redshifts) has a surface brightness of 700 photons cm −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 110 publications
(151 reference statements)
1
19
0
Order By: Relevance
“…They found that future space based experiments with a sensitivity of 3.7×10 −9 erg/s/cm 2 /sr (∼37 mag/arcsec 2 ) will be able to detect hydrogen and helium in intergalactic filaments. Lokhorst et al (2019) have used EA-GLE simulations with a CLOUDY emission model to predict the fluxes from the CGM and IGM and investigated the detectability of faint Hα emission at low redshifts. They found that the Dragonfly Telephoto Array 1 , equipped with suitable narrowband filters, would be able to directly map the cosmic web.…”
mentioning
confidence: 99%
“…They found that future space based experiments with a sensitivity of 3.7×10 −9 erg/s/cm 2 /sr (∼37 mag/arcsec 2 ) will be able to detect hydrogen and helium in intergalactic filaments. Lokhorst et al (2019) have used EA-GLE simulations with a CLOUDY emission model to predict the fluxes from the CGM and IGM and investigated the detectability of faint Hα emission at low redshifts. They found that the Dragonfly Telephoto Array 1 , equipped with suitable narrowband filters, would be able to directly map the cosmic web.…”
mentioning
confidence: 99%
“…For α λ X 10 −2 − 10 −3 , the average intensity given by equation ( 1) may be detectable. Existing IFUs on ∼ 10m optical telescopes are sensitive to surface brightness as low as I λ X ∼ 300 − 1000 γ cm −2 s −1 sr −1 (Martin et al 2010;Morrissey et al 2012;Lokhorst et al 2019), with IFUs on future extremely large telescopes projecting factor of ∼ 3 − 10 improvements (Lokhorst et al 2019). In the UV, a hypothetical Zodiacal background-limited UV space telescope with mirror diameter D and field of view larger than…”
Section: Energetic Considerationsmentioning
confidence: 99%
“…Theoretical work on the CGM has focused primarily on absorption. The number of studies predicting CGM line emission is more limited (van de Voort & Schaye 2013; Corlies & Schiminovich 2016;Sravan et al 2016;Lokhorst et al 2019;Augustin et al 2019;Faerman et al 2020;Corlies et al 2020). The emission picture is further complicated by the fact that galaxy formation simulations -the resource used to predict emission in the vast majority of studiesgenerally do not match the known properties of the CGM, often producing ionic column densities that are off from the observed values by orders of magnitude (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the strongest emission lines, the optical emission from the CGM is expected to be extremely faint; for example, modeling of Hα emission from the CGM at z = 0 (Lokhorst et al 2019) suggests that pushing down to ≈ 10 −19 to 10 −20 erg s −1 cm −2 arcsec −2 will be needed to detect this gas. While this is significantly deeper than current imaging capabilities, the CGM may have significant substructure (see e.g.…”
Section: Narrowband Imaging Of the Circumgalactic Mediummentioning
confidence: 99%